Efficient Calculation of Anharmonic Vibrational Spectra of Large Molecules with Localized Modes. Issue 15 (30th July 2014) - Panek, Paweł T.; Jacob, Christoph R.
Abstract The analysis and interpretation of the vibrational spectra of complex (bio)molecular systems, such as polypeptides and proteins, requires support from quantum‐chemical calculations. Such calculations are currently restricted to the harmonic approximation. Here, we show how one of the main bottlenecks in such calculations, the evaluation of the potential energy surface, can be overcome by using localized modes instead of the commonly employed normal modes. We apply such local vibrational self‐consistent field (L‐VSCF) and vibrational configuration interaction (L‐VCI) calculations to a cyclic water tetramer and a helical hexa‐alanine peptide. The results show that the use of localized modes is equivalent to the commonly used normal modes, but offers several advantages. First, a faster convergence with respect to the excitation level is observed in L‐VCI calculations. Second, the localized modes provide a reduced representation of the couplings between modes that show a regular coupling pattern. This can be used to disregard a significant number of small two‐mode potentials a priori. Several such reduced coupling approximations are explored, and we show that the number of single‐point calculations required to evaluate the potential energy surface can be significantly reduced without introducing noticeable errors in the resulting vibrational spectra.